Combined effects of oregano essential oil and salt on the growth of Escherichia coli in salad dressing - Cattelan, Marília Gonçalves [UNESP]; Nishiyama, Yara Paula de Oliveira [UNESP]; Gonçalves, Tânia Maria Vinturim [UNESP]; Coelho, Alexandre Rodrigo (My University, 2018)
There is a broad research interest in the search for alternatives to chemical additives for use as natural food preservatives. Although many natural compounds have biological in vitro properties evidenced, in situ studies are still scarce. This study evaluated the effect of oregano essential oil (OEO) and salt (NaCl) concentrations against Escherichia coli (ATCC 8739), in salad dressing, using the response surface methodology. The experiment included a 22 central composite rotatable design (CCRD) in a total of 11 formulations of salad dressings. Oregano essential oil was characterized by gas chromatography and salad dressings by ash, lipids, proteins and moisture. OEO was composed mainly by carvacrol (65.1%) and p-cymene (12.0%). Salad dressings showed similar chemical profiles. A mathematical model for the prediction of the antibacterial activity in salad dressing was obtained. The results revealed that the interaction between OEO and salt showed effect on the bacterial count. However, the effect of salt was negative suggesting that the highest NaCl concentrations decreases the bacterial count. Therefore, within the parameters studied, the use of OEO to control E. coli in salad dressing can be considered promising and allows reduction in the levels of salt to be incorporated in food.
Keywords: Antibacterial; Factorial design; Oregano; Spice; Surface response methodology